Penngaruh Pembiayaan Mudharabah dan Musyarakah terhadap Kinerja Keuangan Perbankan Syariah di Indonesia - Irmawati, Nur Arnis Irmawati (Program Studi Akuntansi Lembaga Keuangan Syariah, FEBI, IAIN Parepare, 2024)
Mudharabah financing is income obtained from cooperation between a business between the first party who provides all the capital and the second party who acts as fund manager by sharing business profits in accordance with the agreement stated in the contract, while losses are borne entirely by the sharia bank unless the second party does so. intentional, negligent or breach of agreement. Musyarakah financing is an income obtained from a cooperation agreement between the capital owner and the manager for a particular business, each party agrees to share the profits and provide compensation for funds and risks based on a mutual agreement. This research aims to find out whether musyarakah financing and mudharabah influence the financial performance of Indonesian Sharia Banking. This Research uses associative quantitative methods with data collection techniques in the form of documentation using secondary data, and processing using SPSS version 25. The data analysis techniques for this research are classical assumption testing and hypothesis testing. The research results obtained show 1) FinancingPartial mudharabah does not have a significant influence on financial performance. This is proven by the t-test carried out, where the calculated t value (1.791) < t table (2.06) and a significant value of 0.087 > 0.05 are obtained. 2).Financing Musyarakah has no significant influence on financial performance. This is proven by the t-test carried out, where the calculated t value (0.274) < t table (2.06) and a significant value of 0.786 > 0.05 are obtained. 3). Simultaneouslyfinancingmudharabah and musyarakah have a significant influence on financial performance which has been proven from the F-Test results where the calculated f value (4.244) > f table (3.36) and a significant value of 0.027 < 0.05 are obtained. Keywords: Mudharabah, Musyarakah, Financing, Sharia Bank